Analysis and Validation of the Development of Science Learning Materials Using a Guided Inquiry Model Combined with Carousel Feedback on the Topic of Light Properties - Muslimin Muslimin (Institute of Advanced Knowledge and Science, 2024)
This study aimed to produce valid learning materials on the topic of light properties using the Plomp development model, which consists of five stages: Preliminary Investigation, Design, Realization, Testing, Evaluation, Revision, and Implementation. The model was modified to suit the specific needs of the study. The modification excluded the implementation phase after completing the test, evaluation, and revision stages. The developed learning materials included a Teaching Module based on guided inquiry combined with carousel feedback, Student Worksheets (LKPD), and a Critical Thinking Skills Test. The study focused solely on the validation process, encompassing construct and content validation of the developed materials. The validation was conducted by experts in science education, instructional design, and evaluation measurement. The validation process aimed to ensure that the learning materials met the criteria of validity, relevance, and feasibility for use. Data from the validation process were analyzed descriptively to determine the level of validity of the materials. Based on the validation results, the developed learning materials were declared valid and suitable for classroom use. The final product of this study was a set of learning materials designed not only to support students' understanding of light properties but also to enhance critical thinking skills through the guided inquiry approach and structured feedback. These materials were expected to contribute to improving the quality of science education in schools, particularly in the application of innovative, 21st-century skill-based teaching methods.